Emotion Regulation and Mentalization in People at Risk for Food Addiction. Issue 1 (2nd January 2017) - Innamorati, Marco; Imperatori, Claudio; Harnic, Désirée; Erbuto, Denise; Patitucci, Eleonora; Janiri, Luigi; Lamis, Dorian A.; Pompili, Maurizio; Tamburello, Stella; Fabbricatore, Mariantonietta
ABSTRACT: Researchers investigated the association among food addiction, difficulties in emotion regulation, and mentalization deficits in a sample of 322 Italian adults from the general population. All participants were administered the Italian versions of the Yale Food Addiction Scale (I-YFAS), the Difficulties in Emotion Regulation Scale, the Mentalization Questionnaire, the Binge Eating Scale, and the Michigan Alcohol Screening Test. Of respondents, 7.1% reported high food-addiction symptoms (ie, 3 or more symptoms of food addiction on the I-YFAS). In bivariate analyses, high food-addiction symptoms were associated with more difficulties in emotion regulation and mentalization deficits. In the multivariate analysis, high food-addiction symptoms remained independently associated with mentalization deficits, but not with difficulties in emotion regulation. Our data suggest that mentalization may play an important role in food addiction by making it difficult for an individual to understand his or her own inner mental states as well as the mental states of others, especially when powerful emotions arise.